STUDY OF LITERATURE FINANCIAL TECHNOLOGY, BLOCKCHAIN AND ISLAMIC FINANCE - Erwin SP, M.; Kresna Riady, Dwi; Shabri Abd. Majid, M.; Marliyah, Marliyah; Handayani, Rita (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
FinTech is a new term in the financial industry and its aim is to improve financial services through the use of technology.” Financial technology is one of the most widely used terms for research in the financial industry today. The future of Islamic finance especially Islamic FinTech is very good in Muslim countries. The development of mobile and smartphones has paved the way for FinTech growth in these countries. These opportunities are certainly not without challenges. The biggest challenge for Islamic FinTech companies is about regulation and the lack of good and authentic research in the Sharia Fintech sector. Islamic FinTech needs to keep pace with the rapid developments that occur in the conventional financial world, Islamic FinTech must maintain stability and must protect investors and institutions from fraudulent trading practices.